PENINGKATAN KOMPETENSI SISWA TKJ MELALUI IMPLEMENTASI MIKROTIK DAN PNETLAB UNTUK PERSIAPAN UKK DI SMK LETRIS 1 - Hillman Akhyar Damanik; Merry Anggraeni; Farida Ayu Avisena Nusantari (Jurnal Abdi Insani, 2026)
Background: Pengabdian Kepada Masyarakat (PKM) at SMK Letris 1 focuses on improving the competency of Teknik Komputer dan Jaringan (TKJ) students in the field of computer networking. Currently, students' understanding and configuration of network services remains uneven. This results in low preparedness for the Skills Competency Test (UKK). Therefore, a targeted, hands-on mentoring program is needed. Objective: The PKM aims to improve students' understanding of networking concepts, network device configuration skills, and preparedness for the UKK through direct application on network devices and simulators. Specifically, this activity is aimed at equipping students with competencies in network management using key protocols and features, such as OSPF, VLAN, NAT, Queue, and Proxy. Method: The method used includes providing theoretical material and practical network device configuration using a MikroTik RB941 router and simulations using the PNETLab emulator. Evaluation was conducted through pre- and post-tests to measure students' understanding. Results: The PKM implementation results showed a clear improvement in students' ability to understand and configure computer networks. The average pre-test score, which was initially at 45%, increased to 90% in the post-test. This change indicates that the learning method, which combines theory and practice, was effective. In addition to improving scores, students also demonstrated greater confidence in configuring networks. Therefore, this activity positively impacted students' readiness for the Vocational Competency Test. Conclusion: In conclusion, the implementation of this PKM was effective in improving the skills of TKJ students, both in practical and theoretical aspects.